Inhibition of mitochondrial fragmentation diminishes Huntington’s disease–associated neurodegeneration - Guo, Xing (American Society for Clinical Investigation, 2013)
Huntington’s disease (HD) is the result of expression of a mutated Huntingtin protein (mtHtt), and is associated with a variety of cellular dysfunctions including excessive mitochondrial fission. Here, we tested whether inhibition of excessive mitochondrial fission prevents mtHtt-induced pathology. We developed a selective inhibitor (P110-TAT) of the mitochondrial fission protein dynamin-related protein 1 (DRP1). We found that P110-TAT inhibited mtHtt-induced excessive mitochondrial fragmentation, improved mitochondrial function, and increased cell viability in HD cell culture models. P110-TAT treatment of fibroblasts from patients with HD and patients with HD with iPS cell–derived neurons reduced mitochondrial fragmentation and corrected mitochondrial dysfunction. P110-TAT treatment also reduced the extent of neurite shortening and cell death in iPS cell–derived neurons in patients with HD. Moreover, treatment of HD transgenic mice with P110-TAT reduced mitochondrial dysfunction, motor deficits, neuropathology, and mortality. We found that p53, a stress gene involved in HD pathogenesis, binds to DRP1 and mediates DRP1-induced mitochondrial and neuronal damage. Furthermore, P110-TAT treatment suppressed mtHtt-induced association of p53 with mitochondria in multiple HD models. These data indicate that inhibition of DRP1-dependent excessive mitochondrial fission with a P110-TAT–like inhibitor may prevent or slow the progression of HD.